John : verse by verse - Osborne, Grant R., 1942- (Osborne New Testament Commentaries., 2018)
In John Verse by Verse, respected New Testament scholar Grant R. Osborne invites the reader to become caught up in the dramatic masterpiece of the Fourth Gospel. He writes, "If I were teaching a course in college or seminary on creative writing, John's Gospel would be set alongside Shakespeare as models of brilliant characterization and plot." It is perhaps Osborne's favorite book of the Bible, and enthusiasm for it shines on every page. - Publisher.